Mekanisme Hukum Adat Perdmaian (Mela Sare) Dalam Mewujudkan Rekonsiliasi Para Pihak Pasca Putusan Pengadilan Pada Masyarakat Lamaholot Di Adonara – Flores Timur - Sili, Handrianus David Ola (UI Scholars Hub, 2022)
The substance aspect that underlies this writing in the Adonara community, the implication of a court decision is the breakdown of relations / relations both personal and social between the parties to the dispute or